Making Meaning of Inanimate Objects as Characters in The Blue Umbrella (2013) - Saptiadi , Nur Alifia Putri; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (MOZAIK HUMANIORA, 2023)
This study aims to reveal deeper and different meaning of an inanimate object, specifically umbrella, from naked eye's perspective in The Blue Umbrella Film. The Blue Umbrella Film, an animated short film directed by Saschka Unsled, employs inanimate objects as the characters as seen through the distinct human's facial expression painted on the black, blue, and red umbrellas To pursue the aim of this study, qualitative method was conducted together with Saussure's semiotic theory. The results showed that the black umbrellas signified as the majorities, while the blue and red umbrellas signified as the minorities. The black umbrellas also signified as a group of office workers as well as members of Sexual and Gender Majority. On the other hand, the blue and the red umbrellas signified as the members of Sexual and Gender Minority.  In short, the movie highlights an encouraging message that it  is  okay  to  be different from the majority's choice.